Avaliação ecotoxicológica, bioquímica, histo-hematológica e eficácia de terapêuticos no controle de doenças em Pacu, Piaractus mesopotamicus - Ikefuti, Cynthia Venâncio [UNESP] (2016)
The aims of this research were to estimate the effective and lethal concentration (CE50 and CL50) of imidacloprid (IMD) and of the association between sulfadimethoxin and metronidazole (SM), on eight non-target aquatic organisms; to evaluate the hystopathological effect of the acute exposure to IMD and SM in the gills, liver and kidneys from pacu fish, Piaractus mesopotamicus; to adjust the dose, verify the efficacy of IMD and SM exposure, and to assess the 14 days recovery of experimentally infested pacu fish with Anacanthorus penilabiatus and Aeromonas hydrophila, through the monitoring of the physical and chemical water variables and the hystopathological, hematological, biochemical and immunological response of the fish. The CE and CL50 was above 100.0 mg L-1 for al tested organisms, and the drugs were classified as practically non toxic. After five treatment days with IMD, a significant decrease in parasite count (81.32%) and the increase in erythrocyte number were observed. A reduction in hemoglobin and CHCM count was observed 14 days after the treatment, in the fish exposed to IMD. The SM exposure promoted UFC growth only in the reisolated samples from the healthy and in the non-treated infected fish. The reduction in eosinophils count occurred in all treatments, in comparison to the control. The exposure to SM promoted the increase of Na+ ions in the infected fish. After 14 days, the reduction of burst was observed in all treatments in comparison to the healthy control. All the hystopathological responses observed in the present research were reversible. Both drugs displayed registry potential in Brazilian aquaculture, for reaching the key requirements, such as low toxicity in non-target organisms; significant reduction in the monogenean A. penilabiatus; growth inhibition of the bacteria A. hydrophila in P. mesopotamicus; and promoted reversible changes in the fish